The Impact of Leadership Practices on Total Quality Management and Organizational Performance in the UAE Interior Ministry - Alnuaimi, Abdulla Salem Ahmed; Kamarul Bahari Yaakub (European Journal of Multidisciplinary Studies, 2020)
This study examines the moderating impact of leadership practices (LP) in TQM and organizational performance (OP). Through literature review, four hypotheses were derived which are tested in the UAE to better understand the nature of the relationship between TQM and LP as well as the impact of TQM on OP in the public sector departments in the UAE. Data were collected by distributing questionnaire to 230, data we analyzed by using descriptive and inferential statistics. The research showed the impact of LP on TQM and OP.